Ontologi Hibualamo dalam Perspektif Jurgen Habermas - Nanuru, Ricardo Freedom (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Hibua Lamo is a cultural system that binds communities in North Halmahera.Â It is a form of conflict resolution among the communities by harmonizing interests between conflicting groups as well as binding the groups into a new relationship bond.Â It was tested by riots of Moluccas, including North Halmahera. This study shows that there is a difference context of emergence between Habermass thought and local knowledge of Hibua Lamo. However, based on the Habermass perspective of communication ratio, Hibua Lamo at least get the spirit to a new birth. Based on the new understanding, Hibua Lamo now exists to rely on communicative ratio which is able to withstand annexation of market system and the state, and also to tie the communities in North Halmahera through peace consensus.Keywords: Hibua Lamo, JÃ¼rgen Habermas, local knowledge, communicative ratio.